Analisis Faktor Keterlambatan Pasokan LPG pada PT Pertamina Energy Terminal LPG Tanjung Sekong - Zalfaa, Alyani; Fitriani, Riska; Handayani, Melia; Prasetiowati, Alifia Sri; Ghani, Zaki Abdul; Tsani, Rubby Rahman; Rahmawati, Anisa Yuli (Engineering Faculty at Universitas Singaperbangsa Karawang, 2024)
PT Pertamina Terminal LPG Tanjung Sekong is a company engaged in petrochemicals, more specifically engaged in the management of Liquefied Petroleum Gas (LPG) terminals in Tanjung Sekong, Merak, Banten. The company is a subsidiary of PT Pertamina International Shipping and has been operating since April 2012. Currently, the increase in gas demand in Indonesia is increasing, it means that the Indonesian people still need gas. In this case, PT Pertamina Tanjung Sekong LPG Terminal has a problem with delays in loading and unloading ships in supplying Liquefied Petroleum Gas (LPG). The delay was triggered by several factors, including administrative constraints, bad weather, and too many ship waiting lists. This study used a fishbone diagram method, Root Cause Analysis (RCA), and 5 Whys to identify the root of the problem. The results of the analysis show that improved ship arrival time predictions, more effective administrative handling, and better weather monitoring can reduce LPG gas supply delays. Recommendations include the development of a time-of-arrival prediction system, increased awareness of the accuracy of administrative data, and cooperation with the Meteorology, Climatology, and Geophysics Agency (BMKG) for better weather monitoring.